2022
DOI: 10.1101/2022.05.20.492776
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correcting Modification-Mediated Errors in Nanopore Sequencing by Nucleotide Demodification and in silico Correction

Abstract: The accuracy of Oxford Nanopore Technology (ONT) sequencing has significantly improved thanks to new flowcells, sequencing kits, and basecalling algorithms. However, novel modifications untrained in the basecalling models can seriously reduce the quality. This paper reports a set of ONT-sequenced genomes with unexpected low quality (∼Q30) due to extensive new modifications. Demodification by whole-genome amplification (WGA) significantly improved the quality of all genomes (∼Q50-60) while losing the epigenome.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…We found no coherent methylation motifs in the literature that would fit the observed pattern. Nevertheless, it has been reported that methylated bases can affect the raw signal in the surrounding region [22]. Thus, we can not determine whether multiple methylation motifs are the cause or if an unknown motif is present.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…We found no coherent methylation motifs in the literature that would fit the observed pattern. Nevertheless, it has been reported that methylated bases can affect the raw signal in the surrounding region [22]. Thus, we can not determine whether multiple methylation motifs are the cause or if an unknown motif is present.…”
Section: Resultsmentioning
confidence: 92%
“…Given the notable strides made in direct methylation calling techniques, Oxford Nanopore [22]. Nevertheless, we strongly recommend constantly testing and evaluating reconstructed prokaryotic genomes to avoid erroneous conclusions based on these ambiguous positions introduced by unknown…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the R10.4.1 flow cells (FLO-MIN114), the Rapid Barcoding Kit (SQK-RBK114.24 kit) was used to construct libraries for the rapid sequencing method, and the Native Barcoding Kit (SQK-NBD114.24) was used to construct libraries for the ligation-duplex method. Nanopore raw signal data were basecalled using Dorado 0.5.0 dna_r9.4.1_e8_sup@v3.3, dna_r10.4.1_e8.2_400bps_sup@v4.2.0, and dna_r10.4.1_e8.2_400bps_sup@v4.3.0 models, with or without modification-mediated error correction using the Modpolish toolkit (8).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that base modifications can contribute significantly to base calling errors in ONT sequencing (7,8). Recent developments by ONT, including the introduction of Flowcells (R10.4.1) and Chemistry (SQK-NBD114.24), have demonstrated raw read accuracy exceeding 99.1% (9).…”
Section: Introductionmentioning
confidence: 99%